Creativity in intelligent technologies and data science : second Conference, CIT & DS 2017, Volgograd, Russia, September 12-14, 2017, Proceedings /: second Conference, CIT & DS 2017, Volgograd, Russia, September 12-14, 2017, Proceedings. (2017) - Unknown
No abstract available